Oscillation of certain partial difference equations - Sung Kyu Choi; Bing Gen Zhang (Discrete Dynamics in Nature and Society)
We first obtain sufficiency conditions for the oscillation of all solutions of linear partial difference equation aAm+1,n+1+bAm+1,n+cAm,n+1−dAm,n+Pm,nAm−k,n−1=0. Next, we establish a linearized oscillation result for the nonlinear partial difference equation Am+1,n+1+Am+1,n+Am,n+1−Am,n+Pm,n f(Am−k,n−l)=0.